Brady House - Ghosh, Ayan (2023)
Brady House is located between the Elphinstone Building and HSBC Bank and was formerly known as the Royal Insurance Building. In the past, Brady House was the office of the Bombay Baroda & Central India Railways and later, the Times of India. Currently, it is the office of the Royal Bank of Scotland and the Punjab National Bank.